“La buona novella della morte di Dio”: ricognizioni e campionature dell'opera del “primo” Altizer nella temperie storico-culturale del sessantotto - Mirabella , Giuseppe (Nuovo Giornale di Filosofia della Religione (NGFR), 2021)
This brief essay want to be a concise introduction to the thought of Thomas Altizer, the “first” Altizer (between the Sixties and the Seventies), religious author very prolific. His membership in Theological world of United States is always critical. Altizer is the “prophet” of The-Death-of-God Theme, if one could say so, almost a misunderstood religious genius.